"Big Up West London Crew": One Man's Journey within a Community Rap/Music Therapy Group. Issue 2 (17th December 2016) - Short, Helen
Abstract: This case study describes work undertaken within an NHS early intervention mental health service in the UK, focusing on the therapeutic use of "freestyle" and original rap. In particular, it uses material and analysis pertaining to one individual who formed part of an open group for clients in the community. The specific role of this form of therapy is detailed, addressing the aims of the work relating to the setting and background of the client, and outlines the rationale for the use of an empowerment-based model of working. The clinical material is analyzed from a psychodynamic perspective, with a particular emphasis on the development of the therapeutic relationship and the use of rap as a therapeutic intervention, taking into consideration stylistic and cultural connotations of the genre and Hip Hop culture.